The Application Of Reverse Periodization Model For Improving Leg Muscles Power Ability - Annisa Ariandini Mirage; Dikdik Zafar Sidik; Fitri Rosdiana (Physical Activity Journal (PAJU), 2025)
Reverse periodization is a training plan that starts with high intensity and low volume, and gradually decreases the intensity and increases the volume, or maintains the intensity and increases the volume depending on the sport. The purpose of this study was to determine the Implementation of the Reverse Periodization Model to Increase Leg Muscle Power Ability. The research method used is an experimental research method using the One Group Pre-Test Post-Test Design. The data collection technique was carried out by giving an initial test/pre-test to one experimental group. The study was conducted for 4 weeks with 12 meetings. The implementation of this study used a circuit training method with 12 forms of exercise. The population in this study were 20 trained and active UPI Women's Futsal UKM athletes. The sample used was 14 athletes using a purposive sampling approach. The test instrument used in this study was the vertical jump test. The data analysis test used the paired sample t-test with the IBM SPSS computer application version 25.0. The results of the analysis showed that there was a significant difference between the pretest and posttest on the vertical jump test variable with a sig value. (2-tailed) of 0.002 < 0.05. From the research data, it can be concluded that there is a significant effect of the application of the reverse periodization model on increasing the power capacity of leg muscles.